2021
DOI: 10.1021/acs.jpca.0c10972
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous Nucleation of Butanol on NaCl: A Computational Study of Temperature, Humidity, Seed Charge, and Seed Size Effects

Abstract: Using a combination of quantum chemistry and cluster size distribution dynamics, we study the heterogeneous nucleation of n -butanol and water onto sodium chloride (NaCl) 10 seeds at different butanol saturation ratios and relative humidities. We also investigate how the heterogeneous nucleation of butanol is affected by the seed size through comparing (NaCl) 5 , (NaCl) 10 , and (NaCl) 25 seeds an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 75 publications
1
13
0
Order By: Relevance
“…New particles are generally formed via nucleation, a process in which individual molecules interact with one another until a critical cluster size is reached and particle nucleation becomes favorable . Photoassisted particle formation can be important in many cases, while heterogeneous processes can also be key drivers, as shown in detailed quantum chemical cluster calculations . Molecular precursors for new particle formation and secondary organic aerosol particles can involve the formation of highly oxygenated organic molecules from the oxidation of biogenic terpenes such as α-pinene, and the development of chemical mechanisms to describe this process is critical for climate predictions .…”
Section: New Particle Formationmentioning
confidence: 99%
See 1 more Smart Citation
“…New particles are generally formed via nucleation, a process in which individual molecules interact with one another until a critical cluster size is reached and particle nucleation becomes favorable . Photoassisted particle formation can be important in many cases, while heterogeneous processes can also be key drivers, as shown in detailed quantum chemical cluster calculations . Molecular precursors for new particle formation and secondary organic aerosol particles can involve the formation of highly oxygenated organic molecules from the oxidation of biogenic terpenes such as α-pinene, and the development of chemical mechanisms to describe this process is critical for climate predictions .…”
Section: New Particle Formationmentioning
confidence: 99%
“…2 Photoassisted particle formation can be important in many cases, 3 while heterogeneous processes can also be key drivers, as shown in detailed quantum chemical cluster calculations. 4 Molecular precursors for new particle formation and secondary organic aerosol particles can involve the formation of highly oxygenated organic molecules from the oxidation of biogenic terpenes such as α-pinene, and the development of chemical mechanisms to describe this process is critical for climate predictions. 5 The energetics of peroxide formation from α-pinene were evaluated via conformational sampling using density functional theory.…”
Section: ■ New Particle Formationmentioning
confidence: 99%
“…Moreover, the average granular size is ever-incresing with the amount of deposited Li metal increases (Figure 4d-f; Figure S7c,d employed to account qualitatively for the difference on morphology. For heterogeneous nucleation (molecules/atoms adsorbed on the surface of solid impurities to form crystal nuclei, [34] such as for Li deposited on Cu substrate), the Gibbs free energy of nucleation (ΔG n ) can be expressed as (assumed the new solid phase was sphere of radius r):…”
Section: Electrochemical Performancesmentioning
confidence: 99%
“…Several studies show that QC can be utilized to evaluate thermodynamic properties of charged molecular clusters. However, accurate QC calculations have a high computational cost which constrains their applicability to only small strongly binding molecular clusters. In our previous work, we showed that configurational sampling (CS) only up to a semiempirical level of theory is computationally effective even for large molecular clusters compared to the density functional theory (DFT) or other QC level schemes. Additionally, this method was found to produce similar cluster geometries and qualitatively similar free energy trends compared to those obtained with a combination of density functional theory (DFT, LC-ωHPBE/def2TZVP) with single-point electronic energy at a coupled cluster level (DLPNO–CCSD­(T)/aug-cc-pVTZ) .…”
Section: Introductionmentioning
confidence: 99%
“…In our previous work, we showed that configurational sampling (CS) only up to a semiempirical level of theory is computationally effective even for large molecular clusters compared to the density functional theory (DFT) or other QC level schemes. Additionally, this method was found to produce similar cluster geometries and qualitatively similar free energy trends compared to those obtained with a combination of density functional theory (DFT, LC-ωHPBE/def2TZVP) with single-point electronic energy at a coupled cluster level (DLPNO–CCSD­(T)/aug-cc-pVTZ) . Therefore, in this work, we use this semiempirical level of theory to examine clusters containing even several tens of molecules, which allows us to reveal the molecular mechanism behind the ion-induced nucleation of the studied systems.…”
Section: Introductionmentioning
confidence: 99%